Daya Saing Usaha Warung Tradisional di Tengah Keberadaan Ritel Modern di Kecamatan Bone Kabupaten Bone-Bolango - Nursela Koniyo; Zulkifli Bokiu; Muliyani Mahmud (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine competitiveness, formulate competitive strategies, and find factors causing the decline in the income of traditional stall traders amid the existence of modern retail in Bone District. This research uses qualitative methods with a descriptive approach and uses primary and secondary data sources, the informant in this study is a traditional warung business owner in Bone District. The results showed that traditional stalls in Bone sub-district can compete with modern retail by strengthening the concept of costleadership because it does not require much cost like the concept of differentiation and does not focus consumers and certain areas like the concept of focus. Then the SO strategy can be applied by utilizing existing strengths and opportunities. The factor that causes the decline in the income of traditional stall owners is the lack of insight and careful planning in facing business competition with modern retail.